Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Kepuasan Nasabah Dalam Menggunakan Sistem Online Trading Berbasis Syari’ah: - Sri Aderafika Sani; Purnama Ramadani Silalahi; Muhammad Andre Alkahfi; Aulia Monica Harahap (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
An online trading system is an implementation of stock trading over the internet.. The purpose of this study is to determine the impact of product quality, service quality, and price on customer satisfaction while using a syariah-compliant online trading system provided by PT. Phintraco Sekuritas Cabang Medan. PT. Phintraco Sekuritas Medan's internet trading system is the subject of this investigation. When using an online syariah payment system, product quality does not have a significant impact on how customers feel about their purchases. This is based on the results of data mining. Variable service quality has a significant impact on customer satisfaction when using a halal online trading system, but variable price has no discernible impact on customer satisfaction when using a halal online trading system. Keywords: Sharia Online Trading System, Sharia Stocks, Customer Satisfaction